2011
DOI: 10.1111/j.2044-8260.2011.02024.x
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness‐ and acceptance‐based interventions for anxiety disorders: A systematic review and meta‐analysis

Abstract: MABIs are associated with robust and substantial reductions in symptoms of anxiety and comorbid depressive symptoms. More research is needed to determine the efficacy of MABIs relative to current treatments of choice, and to clarify the contribution of processes of mindfulness and acceptance to observed outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
208
4
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(228 citation statements)
references
References 70 publications
11
208
4
5
Order By: Relevance
“…Our results are consistent with the results of previous studies of mindfulness-based interventions for a range of clinical populations generally (Bohlmeijer et al, 2010;Chiesa & Serretti, 2011;Grossman et al, 2004;Inga, 2011;Klainin-Yobas et al, 2012;Ledesma et al, 2010;McCarney et al, 2012;Piet et al, 2011Piet et al, , 2012Vøllestad et al, 2012) and CHD patients specifically (Griffiths et al, 2009;Sullivan et al, 2009;Tacon et al, 2003). However, ours is the first published study of MBCT for CHD patients in which DSM IV major depression was an inclusion criterion.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results are consistent with the results of previous studies of mindfulness-based interventions for a range of clinical populations generally (Bohlmeijer et al, 2010;Chiesa & Serretti, 2011;Grossman et al, 2004;Inga, 2011;Klainin-Yobas et al, 2012;Ledesma et al, 2010;McCarney et al, 2012;Piet et al, 2011Piet et al, , 2012Vøllestad et al, 2012) and CHD patients specifically (Griffiths et al, 2009;Sullivan et al, 2009;Tacon et al, 2003). However, ours is the first published study of MBCT for CHD patients in which DSM IV major depression was an inclusion criterion.…”
Section: Discussionsupporting
confidence: 82%
“…In a meta-analysis of 6 randomized controlled trials, Piet and Hougaard (2011) found that MBCT significantly reduced the risk of relapse among people with recurring major depression. Results of meta-analyses of MBCT and other mindfulness-based therapies show that these interventions lead to significant improvements in depression, anxiety and other indices of psychosocial adjustment for people with a wide range of physical (Bohlmeijer et al, 2010;Grossman et al, 2004) and mental health (Chiesa & Serretti, 2011;Klainin-Yobas et al, 2012) difficulties, including cancer (Ledesma et al, 2010;Piet et al, 2012), chronic pain (Inga, 2011), anxiety and depressive symptoms (McCarney et al, 2012;Piet et al, 2012), recurrent depression (Piet et al, 2011), anxiety disorders (Vøllestad et al, 2012), and life stress (Chiesa & Serretti, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of 19 studies using a mindfulnessbased treatment approach for various anxiety disorders found large effect sizes for improvements on both anxiety and depression, and a moderate effect on quality of life [41]. Participants of mindfulnessbased treatments have also been very receptive to the use of these techniques for treating their anxiety [42][43][44] and have continued to practice mindfulness techniques at a three-year follow-up [45].…”
Section: Mindfulness To Treat Anxietymentioning
confidence: 99%
“…Mindfulness-Based Stress Reduction has been shown to reduce depression [41,47], improve self-esteem [47,48] and reduce anxiety [41,47]. The founder of the MBSR program and his colleagues conducted the earliest known study published on MBSR as a treatment for anxiety [46].…”
Section: Mindfulness-based Stress Reduction For Anxietymentioning
confidence: 99%
“…applications of mindfulness, and this approach has been widely proven to be effective in treating such disorders in general in several meta-analyses (Hofmann et al, 2010;Chen et al 2012;Vøllestad et al 2012), as well as in helping with a number of individual anxiety disorders, such as general anxiety disorder (Roemer et al, 2008) or social phobia (Piet et al 2010). (4) Depressive disorders are another key domain for applications of mindfulness, where the major effect consists of relapse prevention, and on which basis an important approach to mindfulness, called Mindfulness-Based Cognitive Therapy (MBCT) has been established (Segal, Williams and Teasdale 2002).…”
Section: Research Findings and Research Dilemmasmentioning
confidence: 99%